Clinical presentation and time-course of postoperative venous thromboembolism: Results from the RIETE Registry - Arcelus, Juan Ignacio; Monreal, Manuel; Caprini, Joseph A.; Guisado, Javier Gutiérrez; Soto, Mª José; Núñez, Manuel Jesús; Alvárez, Juan Carlos; the RIETE investigators (Thrombosis and Haemostasis, 2008)
There is little literature about the clinical presentation and timecourse of postoperative venous thromboembolism (VTE) in different surgical procedures. RIETE is an ongoing, prospective registry of consecutive patients with objectively confirmed, symptomatic acuteVTE.In this analysis,we analysed the baseline characteristics, thromboprophylaxis and therapeutic patterns, timecourse, and three-month outcome of all patients with postoperative VTE. As of January 2006, there were 1,602 patients with postoperativeVTE in RIETE: 393 (25%) after major orthopaedic surgery (145 elective hip arthroplasty, 126 knee arthroplasty, 122 hip fracture); 207 (13%) after cancer surgery; 1,002 (63%) after other procedures. The percentage of patients presenting with clinically overt pulmonary embolism (PE) (48%, 48%, and 50% respectively), the average time elapsed from surgery toVTE (22 ± 16, 24 ± 16, and 21 ± 15 days, respectively), and the three- month incidence of fatal PE (1.3%, 1.4%, and 0.8%, respectively), fatal bleeding (0.8%, 1.0%, and 0.2%, respectively), or major bleeding (2.3%, 2.9%, and 2.8%, respectively) were similar in the three groups. However, the percentage of patients who had received thromboprophylaxis (96%, 76% and 52%, respectively), the duration of prophylaxis (17 ± 9.6, 13 ± 8.9, and 12 ± 11 days, respectively) and the mean daily doses of low-molecular-weight heparin (4,252 ± 1,016, 3,260 ± 1,141, and 3,769 ± 1,650 IU, respectively), were significantly lower in those undergoing cancer surgery or other procedures. In conclusion, the clinical presentation, time-course, and three-month outcome ofVTE was similar among the different subgroups of patients,but the use of prophylaxis in patients undergoing cancer surgery or other procedures was suboptimal.
Keywords: Venous thromboembolism; surgery